2020
DOI: 10.17503/agrivita.v42i1.2219
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Selected Plant Extracts to Control Leaf Miner (Lyriomyza spp.) in Chrysanthemum

Abstract: The use of eco-friendly methods in controlling pest and diseases has become an increasing concern in production system in many economically important crops, including ornamentals. The application of plant extract that has an insecticidal effect is considered as one promising alternative in reducing the negative effects of synthetic pesticides. The research was conducted to assess selected plant extracts in several concentrations against leaf miner (Lyriomyza spp.) in chrysanthemum. The experiment was carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…So plant based products are suitable and safe for controlling insect pest on som plants. Rahardjo et al (2020) reported that the application of plant extract that has an insecticidal effect is considered as one promising alternative in reducing the negative effects of synthetic pesticides. They also reported that the respected treatments of Chinese mahogany leaf extract, pyrethrum petal, chinaberry leaf and commercial botanical insecticide Neem Plus also O n l i n e…”
Section: Discussionmentioning
confidence: 99%
“…So plant based products are suitable and safe for controlling insect pest on som plants. Rahardjo et al (2020) reported that the application of plant extract that has an insecticidal effect is considered as one promising alternative in reducing the negative effects of synthetic pesticides. They also reported that the respected treatments of Chinese mahogany leaf extract, pyrethrum petal, chinaberry leaf and commercial botanical insecticide Neem Plus also O n l i n e…”
Section: Discussionmentioning
confidence: 99%
“…Daun tanaman pakcoy yang terjaga dari serangan hama, karena pemberian perlakuan yang tepat akan menunjukkan pembelahan dan pembesaran sel yang terjadi pada tanaman dan kebutuhan hara terpenuhi melalui penyerapan hara oleh perakaran (Ibnusina & Tasnia, 2022). Serta pada penelitian sebelumnya menunjukkan bahwa penerapan ekstrak tanaman atau insektisida nabati yang tepat dapat mengurangi intensitas serangan dan kejadian serta dapat menekan lebih dari 62% serangan penambang daun dan menyebabkan peningkatan produktivitas bunga pada tanaman krisan (Rahardjo, Marwoto, & Budiarto, 2020).…”
Section: Pembahasanunclassified
“…So imidacloprid as small amount may be recommended mixing with plant based insecticides for general use of aphid control in cowpea for its higher efficacy and rapid degradation. Rahardjo et al (2020) reported that the application of plant extract that has an insecticidal effect is considered as one promising alternative in reducing the negative effects of synthetic pesticides.…”
Section: Bio-efficacy Evaluation Of Plant Based Formulation Against A...mentioning
confidence: 99%